2018
DOI: 10.1016/j.jad.2018.02.051
|View full text |Cite
|
Sign up to set email alerts
|

Levels of depression in transgender people and its predictors: Results of a large matched control study with transgender people accessing clinical services

Abstract: This study confirms that non-treated transgender individuals have an increased risk of a depressive disorder. Interventions offered alongside gender affirming treatment to develop interpersonal skills, increase self-esteem and improve social support may reduce depression and prepare individuals for a more successful transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
1
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 87 publications
5
96
1
14
Order By: Relevance
“…The current study found that transgender people who had not undergone any gender affirming medical interventions reported worse outcomes on all GCLS subscales, the global scale, and two clusters than both cisgender people and transgender people who had taken cross-sex hormone treatment and undergone genital surgery (C / -chest reconstructive surgery). These findings support previous research that has shown patients to report less distress with their gender, lower levels of body dissatisfaction, better mental well-being, and greater life satisfaction after they had undergone gender affirming surgery (e.g., Dhejne et al, 2016;Jones et al, 2016;Marinkovic and Newfield, 2017;Marshall et al, 2016;Murad et al, 2010;van de Grift et al, 2018;Witcomb et al, 2018). This study also found that transgender males who had not undergone any gender affirming medical intervention reported worse outcomes on the chest, other secondary sex characteristics, social gender role recognition, psychological functioning, and life satisfaction subscales of the GCLS, as well as the global scale and the two clusters, than transgender males who had taken cross-sex hormone treatment and undergone chest reconstructive surgery.…”
Section: Research Utility Of the Gclssupporting
confidence: 89%
“…The current study found that transgender people who had not undergone any gender affirming medical interventions reported worse outcomes on all GCLS subscales, the global scale, and two clusters than both cisgender people and transgender people who had taken cross-sex hormone treatment and undergone genital surgery (C / -chest reconstructive surgery). These findings support previous research that has shown patients to report less distress with their gender, lower levels of body dissatisfaction, better mental well-being, and greater life satisfaction after they had undergone gender affirming surgery (e.g., Dhejne et al, 2016;Jones et al, 2016;Marinkovic and Newfield, 2017;Marshall et al, 2016;Murad et al, 2010;van de Grift et al, 2018;Witcomb et al, 2018). This study also found that transgender males who had not undergone any gender affirming medical intervention reported worse outcomes on the chest, other secondary sex characteristics, social gender role recognition, psychological functioning, and life satisfaction subscales of the GCLS, as well as the global scale and the two clusters, than transgender males who had taken cross-sex hormone treatment and undergone chest reconstructive surgery.…”
Section: Research Utility Of the Gclssupporting
confidence: 89%
“…Transgender suicide attempt rates, for example, are nine times the national average (45), often worst among transmasculine youth (46). Predictors of depression among transgender people, exacerbated by intersections of race, gender, class, and sexuality (47), include minority stress, low self-esteem, overt discrimination and victimization, lack of social support, and little or no access to medical transition technologies where desired (48)(49)(50). Given higher rates of depression and lower rates of physical activity (51), the study of curiosity within trans populations requires further study (52).…”
Section: Discussionmentioning
confidence: 99%
“…Dissatisfaction with one's birth assigned sex can lead to loneliness and psychological problems (Dhejne et al, 2016;Februari, 2013;Keuzenkamp, 2012;Keuzenkamp & Kuyper, 2013;Testa et al, 2017). Furthermore, prevalence of depression, anxiety, and loneliness in transgender individuals exceeds the prevalence of these conditions in the general population (Bouman et al, 2017;Keuzenkamp, 2012;Witcomb et al, 2018), and both trans men and trans women show an increased prevalence of suicide attempts (Perez-Brumer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%